Biomechanical study of the male lower urinary tract: Simulation of internal and external sphincters dyssynergia. (March 2023) - Wang, Fang; Cao, Zhanhong; Zhai, Lidong; Zhang, Jianguo; Kong, Hu; Lin, Wanying; Fan, Yubo
Abstract: Urethral sphincter dysfunction is an important cause of stress urinary incontinence (SUI). The most effective treatment is the insertion of an artificial urethral sphincter (AUS), which relies to a large extent on the surgeon's experience. However, there is no quantitative standard for cuff tightness, resulting in frequent postoperative complications. This study aimed to investigate the effect of internal and external sphincter dyssynergia on urodynamic parameters in the lower urinary tract. A geometric model of male lower urinary tract tissue was constructed from collodion slices, accounting for the active behavior of the internal and external sphincters. Normal and dyssynergic internal and external sphincters (active sphincter behavior was individually injured by 25%, 50%, 75%, or 100%) were simulated with fluid–structure interactions and changes in urethral stress, displacement, and urine flow rate were detected. We found that when the internal sphincter was injured by 25%, 50%, 75%, and 100%, urethral stress near the internal sphincter decreased by 8.3%, 15.6%, 24.3%, and 35.7%, respectively. Additionally, when the external sphincter was injured by 25%, 50%, 75%, and 100%, urethral stress near the external sphincter was reduced by 13.3%, 24.3%, 38.6%, and 46.6%, respectively. Internal sphincter injury primarily affects positions near the internal sphincter and prostate, while external sphincter injury affects the area between the prostate and urethral outlet. These data could facilitate the standardized evaluation of internal and external sphincter dysfunction and lead to novel methods of preoperative assessment for AUS surgery.